The ripple effect of evidence implementation: a descriptive evaluation of JBI's Evidence-based Clinical Fellowship Program. Issue 2 (5th June 2021) - McArthur, Alexa; Munn, Zachary; Lizarondo, Lucylynn; Porritt, Kylie; Stephenson, Matthew; Stern, Cindy; Lockwood, Craig; Moola, Sandeep; Pearson, Alan; Jordan, Zoe
ABSTRACT: Background: Across healthcare there are acknowledged gaps in the translation of evidence into clinical practice. Undertaking a structured implementation program may assist clinicians to achieve this in their clinical practice setting. Aims/Methods: The current study descriptively evaluates and analyzes the impact of JBI's (formerly known as the Joanna Briggs Institute) Evidence-based Clinical Fellowship program, since its inception in 2005. Results: Since its inception the JBI Evidence-based Clinical Fellowship Program has trained over 560 Clinical Fellows. The program consists of two 1-week intensive training workshops at JBI, collaborating with a JBI Research Fellow facilitator, with each participant then conducting a workplace evidence implementation project over the intervening 6 months in their own clinical setting. A 'train-the-trainer' program was established to provide accredited trainers to run the program through established JBI Collaborating Entities. Conclusion: Implementation of research evidence into the clinical setting is challenging for health professionals. A pragmatic approach adopted through the JBI Evidence-based Clinical Fellowship Program ensures that the Clinical Fellow remains central as the program leader, but has direction and support from their team of various stakeholders, and ongoing collaboration with a JBI facilitator. This ensures increased capacity for engagement and ongoing sustainability of future implementation programs.